Dried distiller’s grains with solubles in steam-flaked or dry-rolled corn diets with reduced roughage levels - May, M.L.; Hands, M.L.; Quinn, M.J.; Wallace, J.O.; Karges, K.K.; Gibson, M.L.; Depenbusch, Brandon E.; Reinhardt, Christopher D.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Distiller’s grains have been used extensively in the U.S. Corn Belt, where producers commonly feed dry-rolled or highmoisture corn. Fuel ethanol production is expanding into the High Plains, where most feedlots flake grain. Compared with dry- rolled corn, steam-flaked corn usually increases or has no change in average daily gain, yields lower dry matter intake and results in 12 to 16% improvement in efficiency. Previous research at Kansas State University and elsewhere suggests that the value of distiller’s grains is different in flaked grain diets than in dry-rolled diets. We think this might be due to lower rumen pH when flaked grains are fed, perhaps reducing digestibility of the diet, especially the fibrous components. Because distiller’s grains contain considerable amounts of fiber, it might be possible to add less roughage to finishing diets that contain distiller’s grains, and doing so, improve efficiency.
Keywords: Beef; Cattle; Distiller’s grains; Reduced roughage levels